The Relationship Between Body Mass Index and Body Image Among Adolescent Students - Maulidya Ayumi; Roxsana Devi Tumanggor (Caring: Indonesian Journal of Nursing Science, 2024)
Adolescence is a period marked by significant changes, including physical changes such as alterations in body mass index (BMI). Deviations in BMI from expected norms can impact an adolescent's body image. This study aims to examine the relationship between BMI and body image among male and female adolescents at SMAN 2 Kisaran. The research employed a quantitative approach with a descriptive correlational design. The population for this study included 648 adolescents, with a sample size of 247 respondents selected through proportionate stratified random sampling. We tested the correlation using the Spearman correlation test. The results indicate that adolescents with a normal BMI tend to have a positive body image (95 individuals, 38.5%), while those with an obese BMI tend to have a negative body image (17 individuals, 6.9%). The analysis showed a statistically significant relationship between BMI and body image, with a p-value of 0.00, less than the alpha value of 0.05. This study highlights the importance of parental and educational roles in providing education about ideal body shapes and suggests the establishment of counseling services to support mental health and self-esteem related to body image among adolescents.